2007
DOI: 10.1002/dvdy.21169
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear accumulation of β‐catenin and transcription of downstream genes are regulated by zygotic Wnt5α and maternal Dsh in ascidian embryos

Abstract: Nuclear ␤-catenin plays crucial roles in the establishment of the embryonic axis and formation of mesendoderm tissues in ascidians and other animals. However, the cue responsible for nuclear accumulation of ␤-catenin in the vegetal hemisphere is still unknown in ascidians. Here, we investigated the roles of Wnt5␣ and Dsh in the nuclear accumulation of ␤-catenin and activation of its downstream genes in the ascidian Halocynthia roretzi. Wnt5␣ knockdown embryos lost nuclear accumulation of ␤-catenin at the 64-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 60 publications
(49 reference statements)
2
25
0
Order By: Relevance
“…The regulated stabilisation of bcatenin is required to specify endomesodermal fate and leads to activation of a specific transcriptional regulatory network that is responsible for fate specification and differentiation. A very similar situation has been described in other deuterostomes (other echinoderms and in ascidians that belong to chordates) (Imai et al, 2000;Kawai et al, 2007;Miyawaki et al, 2003). In bilaterians outside of deuterostomes, the function of the Wnt/b-catenin pathway has been deciphered in great detail in the ecdysozoan model systems C. elegans and D. melanogaster, in which it is involved in different aspects of anteroposterior polarity.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The regulated stabilisation of bcatenin is required to specify endomesodermal fate and leads to activation of a specific transcriptional regulatory network that is responsible for fate specification and differentiation. A very similar situation has been described in other deuterostomes (other echinoderms and in ascidians that belong to chordates) (Imai et al, 2000;Kawai et al, 2007;Miyawaki et al, 2003). In bilaterians outside of deuterostomes, the function of the Wnt/b-catenin pathway has been deciphered in great detail in the ecdysozoan model systems C. elegans and D. melanogaster, in which it is involved in different aspects of anteroposterior polarity.…”
Section: Introductionsupporting
confidence: 56%
“…The Wnt/b-catenin pathway is activated at the vegetal pole As knockdown of b-catenin leads to animalized embryos in both ascidians and sea urchins (Imai et al, 2000;Kawai et al, 2007;Logan et al, 1999;Wikramanayake et al, 1998), we tested whether this pathway had a similar function in S. kowalevskii. When the Wnt/b-catenin pathway is activated, b-catenin protein becomes stabilized and translocates to the nucleus where it activates transcriptional targets.…”
Section: Research Articlementioning
confidence: 99%
“…-catenin, in turn, activates a gene regulatory network that leads to specification of the endoderm (Davidson et al, 2002a). It has been suggested that the role of -catenin in specification of the endomesodermal germ layer might reflect an ancestral function because it is conserved in other deuterostomes and in cnidarians (Kawai et al, 2007;Momose and Houliston, 2007;Wikramanayake et al, 2003). In vertebrates, however, TGF signals, not Wnts, appear to be the primary inducers of the endoderm.…”
Section: Nodal Signalling and Endoderm Formationmentioning
confidence: 99%
“…The knockdown (KD) of pem-1 causes irregular cleavages of the posterior blastomeres because the centrosome-CAB linkage is interrupted, owing to collapse of the microtubule bundles that connect them (Negishi et al, 2007;Prodon et al, 2010). Furthermore, although -catenin normally accumulates in the nucleus of only the vegetal somatic blastomeres, where it regulates the expression of -catenin/TCF-dependent genes during the cleavage stages (Imai et al, 2000;Kawai et al, 2007), pem-1 KD in H. roretzi embryos causes the nuclear accumulation of -catenin in the germline blastomeres, resulting in the ectopic expression of -catenin/TCF-dependent genes, such as FoxA-a, FoxD and FGF9/16/20 (Kumano and Nishida, 2009). Therefore, Pem-1 regulates, directly or indirectly, the position of cleavage planes and -catenin/TCF-dependent transcription.…”
Section: Introductionmentioning
confidence: 99%